Switching of the mechanism of charge transport induced by phase transitions in tunnel junctions with large biomolecular cages. Issue 33 (8th March 2021) - Gupta, Nipun Kumar; Pasula, Rupali Reddy; Karuppannan, Senthil Kumar; Ziyu, Zhang; Tadich, Anton; Cowie, Bruce; Qi, Dong-Chen; Bencok, Peter; Lim, Sierin; Nijhuis, Christian A.
Abstract : This work gives new insights in the conduction mechanisms across biomolecular junctions and demonstrates that proteins can reversibly change between in- and coherent tunnelling pathways defined by the protein cage and the amount of co-factor. Abstract : Tunnel junctions based on Fe storing globular proteins are an interesting class of biomolecular tunnel junctions due to their tunable Fe ion loading, symmetrical structure and thermal stability, and are therefore attractive to study the mechanisms of charge transport (CT) at the molecular level. This paper describes a temperature-induced change in the CT mechanism across junctions with large globular (∼25 nm in diameter) E2-proteins bioengineered with Fe-binding peptides from ferritin (E2-LFtn) to mineralise Fe ions in the form of iron oxide nanoparticles (NPs) inside the protein's cavity. The iron oxide NPs provide accessible energy states that support high CT rates and shallow activation barriers. Interestingly, the CT mechanism changes abruptly, but reversibly, from incoherent tunnelling (which is thermally activated) to coherent tunnelling (which is activationless) across the E2-LFtn-based tunnel junctions with the highest Fe ion loading at a temperature of 220–240 K. During this transition the current density across the junctions increases by a factor of 13 at an applied voltage of V = −0.8 V. X-ray absorption spectroscopy indicates that the iron oxide NPs inside the E2-LFtn cages undergo a reversible phase transition; this phase transition opens up new a tunnelling pathway changing the mechanism of CT from thermally activated to activationless tunnelling despite the large size of the E2-LFtn and associated distance for tunnelling.